Prevalence of neonatal thrombocytopenia in five cities of India: A cross-sectional descriptive study - Parmila Malik; Atul Khajuria; Khattri , Jyotsana; Singh , Lalit; Veeresh VG (Asian Journal of Medical Sciences, 2023)
Background: Neonatal thrombocytopenia is defined as a platelet count <150,000/μL can be mild, moderate, or severe thrombocytopenia. The platelet production in neonates begins early at 5 weeks of gestation and reaches the adults count by 24–28 weeks. The platelet disorders are due to impaired platelet production or increased platelet destruction and sequestration. The onset of neonatal thrombocytopenia occurs within 72 h and late onset develops the risk of intraventricular hemorrhage. Hence, the knowledge regarding the incidence and occurrence is vital. Aims and Objectives: The present study aims to study the prevalence of neonatal thrombocytopenia in India. Materials and Methods: A cross-sectional descriptive study was designed, A total of 3250 neonates were assessed for the prevalence of neonatal thrombocytopenia using non-probability convenient sampling technique studies at various cities such as Lucknow, Panipat, Sonipat, Gohana, and Delhi. The data relating to levels of platelets were assessed for all the samples. Results: The present study revealed that the prevalence rate of neonatal thrombocytopenia was 3.4% at various cities in India. Conclusion: The present study assessed the prevalence of neonatal thrombocytopenia this determines the early intervention and prevention of the complication in relation to neonatal thrombocytopenia.